Improving Review Text Writing Competence via Digital-Based Differentiated Instruction for Junior High School Learners - Taufik Hidayat; Rina Agustini; Herdiana, Doni (Universitas Swadaya Gunung Jati, 2025)
This study aims to improve students’ review text writing skills through a digital-based differentiated learning approach. This classroom action research was conducted in two cycles at SMP Negeri 4 Manonjaya with 25 students as participants. Each cycle consisted of planning, action, observation, and reflection stages. Differentiated learning was implemented by adjusting the content based on students’ interests in the review objects (short films and picture story videos), which were then presented in the form of digital posters. Data were collected through observation, interviews, and documentation, and analyzed descriptively and qualitatively. The results revealed a significant improvement in the aspects of content, structure, language, and format of review texts. The average score increased from 73 in Cycle I to 89.5 in Cycle II, with learning mastery improving from 52% to 100%. The findings indicate that digital-based differentiated learning is effective in enhancing review text writing skills as well as increasing students’ participation and learning motivation.